Changing roles in forest research - Sayer, Jeffrey A. (1998)
The globalisation of economies and the emergence of a powerful multi-national corporate sector will result in significant shifts in the geographic locations, types and intensities of forest use. Governments will increasingly need to apply their resources to creating the optimal policy environment. New types of forest research institutions and a new culture of forest research are required: science that operates at the scale of landscapes allowing the optimisation of many products, and that treats forests in their social context; and management that can adapt quickly to changing social and economic conditions. Tropenbos' special contribution may be to develop the capacity to predict the response of these systems to a variety of management interventions. CIFOR's contribution lies in drawing on the information produced by Tropenbos and other upstream science to generate options for institutional and policy interventions to achieve sustainable forestry. Future research should give increased emphasis and resources to achieving greater integration to research management within each site. Optimal utility of the residual forests will come from an appropriate balance between management for environmental functions and for the variety of products whose harvesting is consistent with the maintenance of these environmental functions. The future role of public forest research institutes should be to provide the scientific underpinnings for multiple use forest management with a heavy emphasis on environmental public goods and the equitable distribution of costs and benefits.